Ligand free, highly efficient synthesis of diaryl ether over copper fluorapatite as heterogeneous reusable catalyst - Mulla, Shafeek Abdul Rashid; Inamdar, Suleman M.; Pathan, Mohsinkhan Y.; Chavan, Santosh S. (Tetrahedron Letters, 2012)
A novel ligand-free, highly efficient, and an inexpensive method has been developed by using ecofriendly, heterogeneous reusable copper fluorapatite (CuFAP) catalyst for the synthesis of diaryl ethers from the cross coupling reaction of the various substituted aryl halides (fluoride, chloride, bromide, and iodide) with the potassium salts of various substituted phenols in the presence of N-methyl 2-pyrrolidone (NMP) as a solvent at 120 degrees C. The protocol obtained the corresponding cross coupling products in good to excellent yield. The CuFAP catalyst was recovered by simple filtration from the reaction mixture and reused several times without the loss of catalytic activity. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Arylhalide; Copper fluorapatite; Diaryl ethers; phenol; Ullmann coupling